Omission of postoperative cystoscopic assessment may be hazardous: A case report of bladder injury secondary to laparoscopic Burch-type colposuspension - (:unkn) unknown (My University, 1999)
Careful and systemic cystoscopy must be performed following any vaginal, abdominal, or laparoscopic type incontinence operation. Herein, we present a case of a patient suffered bladder perforation, a potential complication of laparoscopic intervention, which could have been easily prevented or managed intraoperatively. On account of this occasion, the significance of check cystoscopies after incontinence operations is revisited.